Re-Alice: Reimagination of Carroll’s Alice in Wonderland into Animation and Live Action - Oktavian, Nurrisda Hermin; Zabrina, Elga Lauris; Alisya, Nanda Shabrina (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2024)
Walt Disney Pictures has adapted several famous animated cartoons into live-action films in recent years, including Alice in Wonderland. The film is based on Lewis Carroll's classic novel, which tells the story of Alice's adventures in Wonderland. The adaptation process brought several changes in the form of the latest story. This study uses a qualitative descriptive method to investigate and examine the reimagination markers and reimagination functions from the animated film Alice in Wonderland (1951) to the live-action version (2010). This study utilizes the reimagination theory of Purnomo et al., which categorizes markers into mutations and presences in textual, visual, and operative elements. These markers allow the work to fulfill various functions, including Stylistic, Ludic, Metathetic, Media, Branding, and Cultural Functions. This study found significant variations between the 1951 animated and 2010 live-action versions of Alice in Wonderland. The most common reimagination markers were in the visual elements. Meanwhile, the stylistic function is most frequently found in the function section. The findings of this study are likely to provide an additional and new understanding of cinematic adaptation and literary reimagination.